Evaluation in vitro de l’effet insecticide du romarin (Rosmarinus officinalis) et de la sauge (Salvia officinalis) vis-à-vis du puceron vert des agrumes (Aphis spiraecola). - OUSAADI, YOUCEF; MOUKDAD, NAIL (My University, 2019)
Aphids are classified today among the most disastrous insect pests of citrus seen the colossal damage and the economic losses that the colonies of this insect cause. In the hope of finding new biological alternatives to the harmful chemical means in order to eliminate this permanent peril, an initial experimentation of two biological tests was conducted; mortality and repulsion test of methanoid extracts of rosemary (rosmarinus officinalis) and sage (Salvia officinalis) on adults of the green citrus aphid Aphis spiraecola. The test asserted that the extracts tested caused the mortality and repulsion of the aphidien populations. The mortality was in perfect increase on the one hand with the duration of exposure to the biocides, and on the other hand with the dose administered. It was also confirmed that rosemary extract had a lethal effect (LD50: 0.26%) and repellent (PR: 40%) much more than the extract of sage (LD50: 2.71%, PR: 26.66%). Thus, the methanolic extract of can annihilate 50% of Aphis spiraecola in a dose of 0.26% after five days of exposure to the pesticide only.
Keywords: Citrus; Aphis spiraecola; Biological control; Rosemary (Rosmarinus officinalis) Sage (Salvia officinalis); Bio Insecticides.